Adaptation of traditional Malay house design towards housing comfort and satisfaction - Syazwani Ahmad; Aprodita Emma Yetti; Nor Eeda Ali; Mohamad Sofiyuddin Sanusi; Puteri Yuliana Samsudin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Prioritizing of environmental and socio-cultural factors of the community in housing design will be able to create a home that is natural and flexible with various conditions and lives of its occupants from time to time. Thus, will be able to provide comfort and satisfaction of housing to its occupants. This study aims to review and identify the design and concept of traditional Malay houses that suitable to be applied in modern housing development towards improving the occupant’s comfort and satisfaction aspects The literature review has identified several factors in comfort and satisfaction of the housing occupants such as house design, house and space size, space flexibility, space arrangement, space allocation, lighting and ventilation. Traditional Malay houses design are referred as a comparison factor for this study as a basic element of housing comfort and satisfaction. The approach of the study involves a quantitative and a qualitative approach. The analysis led to the discovery of the problems of modern house design from various aspects which including design, size, space arrangement, lighting and ventilation. Therefore, the recommendation is to adapt potential traditional Malay house design elements in modern housing development. The study concludes that the adaptation of potential elements of traditional Malay house design can produce a sustainable housing, offering comfort and satisfaction, improve the quality of life and gives good implications for housing development.